Model for the Management of State Higher Education Institutions [In Bulgarian] - B.V. Toshev (University of Sofia, 2018)
The Act of Higher Education was adopted in 1995. With it, Bulgaria became part of the European educational area, where higher education is structured in three cycles: (1) the basic one leading to the Bachelor's degree; (2) additional qualification and specialization leading to the Master's degree and (3) scientific training which ends with the educational and scientific degree "doctor". Over the years, this Act has shown defects mainly related to the inability of the state to exercise control over the activities of state higher education institutions, which is often not of public interest. That is why the adoption of a new Act on Higher Education is a pressing necessity. This article offers a new model of state university management.